Pola Tanam Tumpang Sari di Desa Satar Punda Barat, Kabupaten Manggarai Timur, Provinsi Nusa Tenggara Timur - Marlinda Mulu; Rudolof Ngalu; Fransiskus Laka Lazar (Institut Pertanian Bogor, 2020)
West Satar Punda Village has horticultural farming potential that needs to be developed because it has fertile land, however most farmers are only familiar with monoculture farming system. They are not familiar with the polyculture farming system, thus farmers' income depends only on one type of crop during harvest season. The advantages of polyculture farming system are it can be planted two or more types of plants on the same land and the frequency of harvest is more than once. The purpose of this program is to introduce intercropping pattern (polyculture) by optimizing land by growing more than one type of plants (tomatoes and red chili) and increasing the welfare of farmers with the nearly simultanuous harvest time of the two types of plants. The method used were extension techniques and demonstration method in a plot of sample land. The results of the program show positive responses and increased knowledge about intercropping pattern of the members of farmers group, and also increases farmer's income.